Living with complexity - Norman, Donald Arthur, 1935- (Cambridge : MIT, 2011)
If only today's technology were simpler! It's the universal lament, but it's wrong. We don't want simplicity. Simple tools are not up to the task. The world is complex; our tools need to match that complexity. Simplicity turns out to be more complex than we thought. In this provocative and informative book, Don Norman writes that the complexity of our technology must mirror the complexity and richness of our lives. It's not complexity that's the problem, it's bad design. Bad design complicates things unnecessarily and confuses us. Good design can tame complexity. Norman gives us a crash course in the virtues of complexity. But even such simple things as salt and pepper shakers, doors, and light switches become complicated when we have to deal with many of them, each somewhat different. Managing complexity, says Norman, is a partnership. Designers have to produce things that tame complexity. But we too have to do our part: we have to take the time to learn the structure and practice the skills. This is how we mastered reading and writing, driving a car, and playing sports, and this is how we can master our complex tools. Complexity is good. Simplicity is misleading. The good life is complex, rich, and rewarding-but only if it is understandable, sensible, and meaningful.
Keywords: Complexiteit ; maatschappij